Quantification of antioxidant and antimicrobial properties of oil palm empty fruit bunch lignin based on organosolv extraction - Thanapimmetha, Anusith; Kingkaew, Wipawan; Myint, Ni Ni; Sakulshah, Netipon; Khomlaem, Chanin; Saisriyoot, Maythee; Srinophakun, Penjit (Agriculture and Natural Resources, 2024)
Importance of the work: Lignin from an oil palm empty fruit bunch (OPEFB) sample was extracted using an organosolv technique to characterize the antioxidant and antimicrobial properties. Objectives: To optimize the OPEFB extraction conditions for lignin using different mixtures of organic acid solution and extraction times. Materials & Methods: OPEFB samples were pretreated using dilute sulfuric acid, followed by organosolv extraction. The most effective extraction conditions were identified for producing lignin. This lignin was characterized based on Fourier-transform infrared (FTIR) spectroscopy and various properties, including molecular weight, particle size, total phenolic content (TPC) and antioxidant and antimicrobial activities. Results: The study involved pretreating OPEFB with 8% (volume per volume) sulfuric acid, then extracting with different mixtures of organic acid containing formic acid (FA), acetic acid (AA), and water (H2O) and using different extraction durations. The optimal extraction conditions were achieved by combining FA/AA/H2O in the ratio 30:60:10% (volume per volume per volume) and maintaining it for 60 min. The mean (± SD) effectiveness of lignin extraction was 44.1 ± 0.06%. The purity of the extracted lignin was 92.2 ± 0.21%, comprising 91.0 ± 0.22% acid-insoluble lignin and 1.16 ± 0.02% acid-soluble lignin. The produced lignin had a small molecular size and most functional groups were phenol hydroxyl groups, which affected the antioxidant and antimicrobial activities. Main finding: The organosolv technique showed potential for lignin extraction from OPEFB. This method not only uses greener chemicals compared to conventional approaches but also identified antioxidant and antimicrobial activities as a way of adding value to agricultural waste materials.